MEDICAL AND SOCIAL CHARACTERISTICS OF COVID-19 DISEASE IN THE POPULATION - Abdullaev I. K.; Reimberganov J. I; Matyakubov Zh. R (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
For almost all countries of the world, including Uzbekistan, 2020 the COVID-19 pandemic has become a major examining year for the World Health Organization and the health systems of each country, and this process continues in 2021. It has been practically proven that no country in the world is ready for this process. The Hubei Province of Wuhan, China was the starting point for the COVID-19 pandemic, which spread throughout the world in six months. The purpose of the study is to study and evaluate some of the medical and social aspects of the spread of COVID-19 among the population in the Khorezm region. 226 people participated in this research; of these, 123 were infected with COVID -19; 103 were not infected and 66% live in cities of which 33.4% in rural areas. The spreading speed largely depends on the human factor, while the role of natural and geographical factors is not revealed. That is, its prevalence among the population was directly related to the strict observance of the established sanitary and hygienic rules by people.